Penguatan Pusat Pemulihan Aset (PPA) : Langkah Strategis Percepatan Pemulihan Kerugian Negara Akibat Tindak Pidana Korupsi: Ditinjau Dari Perbandingan Sistem Hukum - Soeherman Soeherman; Tuti Widyaningrum; Cecep Suhardiman (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This purpose of this research is to examine the comparative implementation of Common Law, Civil Law, Religious Law, Customary Law, and Socialist Law systems in terms of the effectiveness of the asset recovery process and the strategic role of the Asset Recovery Center (PPA) in accelerating the recovery of state losses caused by corruption. This research adopts a juridical-normative approach, which is a legal study conducted by examining literature or secondary data as the basis for analysis.The results of the study indicate that in the context of strengthening the role of the Asset Recovery Center as a measure to accelerate the reduction of state losses due to corruption, each legal system has its advantages and challenges. Common Law is flexible and innovative in handling complex cases. Civil Law provides legal certainty through clear codification. Religious Law offers strong moral values but faces challenges in social adaptability and political interference, requiring an inclusive approach. Customary Law prioritizes traditional values and collaboration with customary leaders but experiences difficulties in legal consistency across regions. The Socialist Law system emphasizes social justice and wealth redistribution but faces challenges of political influence and complex bureaucracy.